Ultrasound is better tolerated than vaginal examination in and before labour. (19th July 2018) - Usman, Sana; Barton, Helen; Wilhelm‐Benartzi, Charlotte; Lees, Christoph C.
Abstract : Background: Intrapartum ultrasound has been proposed as a method of assessing labour progress but its acceptability has not been comprehensively assessed. Aims: We evaluated the acceptability of intrapartum ultrasound in women having vaginal examination (VE) and ultrasound (US) assessment (transabdominal (TA) and transperineal (TP)) prior to delivery, with and without regional analgesia (RA). Materials and Methods: Women at 24–42 weeks gestation were included in a prospective observational cohort study. The acceptability of digital VE and TP US were assessed pre‐ and post‐examination using the modified validated Wijma Delivery Experience Questionnaire. Acceptability scores ranged 6–36 (6 being most and 36 being least positive) in six domains: positive‐trust and relax, negative‐harmful to baby, worrying, painful, intrusive. Results: Of 119 women recruited, 104 completed both pre‐ and post‐assessment questionnaires. Eighty‐nine per cent of women were nulliparous with median gestation 40 + 2 weeks (25–42 +1 ). Thirty‐two per cent had RA before assessment, 91% in total. The combined acceptability scores of both negative and positive experiences (6 = most acceptable, 36 = least acceptable) for VE and US pre‐assessment were 15 and 7 respectively ( P < 0.0001: Mann‐Whitney U ‐test). VE was associated with less positive / more negative domain scoring post‐assessment 12 and 6, respectively ( P < 0.0001). Although RA made no difference to the perceived experience pre‐VE ( P = 0.9), post‐VE, women with RAs considered VEs more acceptable than those without RA ( P = 0.0022). Conclusion(s): This is the first study to comprehensively assess the acceptability of VE and intrapartum US. US assessment prior to delivery is more acceptable than VE. RA ameliorated the negative experience of the VE post‐assessment.